Organisasi Registrasi Kanker Population-Based di Indonesia - Soeripto, Soeripto (Universitas Gadjah Mada, 1985)
Based on technique of cancer registration there are three types of cancer registry. These types are: 1.pathology department-based cancer registry 2.hospitl -based cancer registry 3. population-based cancer registry. Each of these types has its own method and characteristics. The aim of pupulation-based cancer registry is ib evaluate and control the trends of cancer in the community. This field has very close relation with cancer epidemiology. The prospect of the population-based cancer registry in Indonesia depends on various conditions. It is concluded that the Special Province of Yogyakarta could fulfill the conditions for the purpose of developing population-based cancer registry in Indonesia, while Bali is an ideal place for population-based cancer registry in Indonesia. Therefore, other conditions are needed for this purpose. Key Words: population-based cancer registry - technique of cancer registration - characteristics of cancer registry - cancer control in the community - cancer epidemiology